2019
DOI: 10.3389/fnagi.2019.00254
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neurofilament Light Chain as a Potential Biomarker for Alzheimer's Disease: A Correlative Meta-Analysis

Abstract: Neurofilament light (NFL) is a putative biomarker of neurodegeneration. This study evaluates the correlative association of NFL with Alzheimer's disease (AD) indices. Relevant studies were identified after a literature search in electronic databases and study selection was based on pre-determined eligibility criteria. Correlation coefficients between NFL levels and important AD indices reported by individual studies were pooled as z-scores. Meta-regression analyses were performed to evaluate the relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 54 publications
6
69
1
4
Order By: Relevance
“…The neurofilament heteropolymers are the primary cytoskeleton proteins predominantly found in axons. Among the four subunits, namely the three isoforms NFL, neurofilament medium and neurofilament heavy, and alpha-internexin, NFL is the most abundant [ 59 , 62 ]. Forming the core of the neurofilament, NFL is a triplet protein essential to the structure of the myelin that surrounds the axons within the central nervous system [ 62 , 63 ].…”
Section: Cerebrospinal Fluid Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…The neurofilament heteropolymers are the primary cytoskeleton proteins predominantly found in axons. Among the four subunits, namely the three isoforms NFL, neurofilament medium and neurofilament heavy, and alpha-internexin, NFL is the most abundant [ 59 , 62 ]. Forming the core of the neurofilament, NFL is a triplet protein essential to the structure of the myelin that surrounds the axons within the central nervous system [ 62 , 63 ].…”
Section: Cerebrospinal Fluid Biomarkersmentioning
confidence: 99%
“…Forming the core of the neurofilament, NFL is a triplet protein essential to the structure of the myelin that surrounds the axons within the central nervous system [ 62 , 63 ]. As their presence within the CSF is specific for axonal injury, elevated NFL concentrations have been widely reported in neurodegenerative disorders, especially in AD patients [ 59 , 62 , 63 , 64 ]. While the mechanisms of NFL aggregation are still unelucidated, they are thought to be similar to the hyperphosphorylation process of tau proteins [ 65 ].…”
Section: Cerebrospinal Fluid Biomarkersmentioning
confidence: 99%
“…T-tau had the strongest association with cognition in the presence of amyloidosis; followed by Ng. Variables associations with NfL did not differ by amyloid status [38].…”
Section: The Interaction Between the Proteins And Association With Nementioning
confidence: 68%
“…NFL and YKL-40 were associated with Aβ+ in non-demented individuals only [37]. CSF YKL-40 was positively associated with both CSF NFL and T-Tau [38]. Jin M [39] reported that CSF NFL levels correlated with total tau, phosphorylated tau, and neurogranin but not with beta amyloid (Aβ).…”
Section: The Interaction Between the Proteins And Association With Nementioning
confidence: 99%
“…Neurofilaments accumulate specifically in the cell bodies and proximal areas of neurons during neurological disorders (Liu et al, 2009). The concentrations of NFL is increased both in the plasma (Lin et al, 2018) and CSF (Jin et al, 2019 in AD. The level of CSF NFL increases as a function of age (Bacioglu et al, 2016) in mice model of Aβ amyloidosis, while NFL deficiency aggravates amyloid pathology in NFL knock out (KO) mice (Fernandez-Martos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%